SCIENTIFIC AND METHODOLOGICAL SUPPORT OF JUDOISTS TRAINING - Tsysar, A.O.; Maltsev, G.S.; Zekrin, F.Kh.; Zekrin, A.F. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify effective means and methods for diagnosing physical qualities and functional state in the process of sports training of judo wrestlers. Methods and structure of the study. The scientific experiment was carried out with the help of a theoretical analysis of scientific and methodological literature and generalization of the experience of the scientific and medical center of the Chaikovsky State Academy of Physical Culture and Sports. Results and conclusions. As a result of the experiment, a program of scientific and methodological support for the training of judokas was developed, based on the diagnostic potential of the scientific laboratory of the Tchaikovsky State Academy of Physical Culture and Sports and including the following sections: morphology, physical, technical-tactical, functional and psychological readiness. The program of scientific and methodological support for the training of judoists is implemented at all stages of the long-term development of sportsmanship within the framework of ongoing, milestone comprehensive surveys, as well as surveys of competitive activity.